A Conceptual and Therapeutic Analysis of Fear - Starkstein, Sergio (Springer International Publishing, 2018)
There is an important gap in the philosophical literature concerning the concept of fear and its remedies, and this book has been designed to examine different concepts of fear that inform its therapy. Structured as a historical-philosophical investigation of the concept of fear, this book is not a purely historical analysis of fear but also provides a broad brushwork rendition of the main concepts of fear as presented by selected philosophers and thinkers, and how they have approached its therapy.